FAKTOR DETERMINAN KEMISKINAN DI PROVINSI NUSA TENGGARA TIMUR TAHUN 2015-2019 - Yulyanah (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
Poverty is one of the phenomena that occurs in all developing countries and is a big problem for the government to deal with. East Nusa Tenggara Province is the third poorest province in Indonesia. This study aims to analyze the factors that influence poverty levels in East Nusa Tenggara Province. The research data used secondary data obtained from BPS and the Ministry of Finance, namely Gross Regional Domestic Product (GRDP), data on government spending in education, access to proper drinking water and sanitation facilities, the Gender Empowerment Index (IDG), and real per capita spending. The method uses panel data regression analysis using data from 2015–2019 in regencies and cities in East Nusa Tenggara Province. The results of panel data regression show that in 2015–2019, the independent variables that have a significant effect on poverty levels in East Nusa Tenggara Province are GDRP, decent drinking water sources, decent sanitation facilities, gender equality, and per capita real expenditure. Meanwhile, what does not have a significant effect on the poverty rate is government expenditure on education. Together, the variables of GRDP, government expenditures in the education sector, access to proper drinking water and sanitation facilities, gender equality, and per capita real expenditure have a significant effect on the poverty level.